A Hopping Robot Driven by a Series Elastic Dual-Motor Actuator - Verstraten, Tom; Furnemont, Raphael; Vanderborght, Bram; Lefeber, Dirk; Beckerle, Philipp (IEEE Robotics and Automation Letters, 2019)
In this letter, we present the kinematically redundant series elastic dual-motor actuator (SEDMA). It consists of two motors, coupled to a series spring through a planetary differential. The redundant degree of freedom of this system can be exploited to optimize a specific aspect of the actuation task. This requires a controller, which distributes the required output power among the two different inputs in an optimal way. The closed-loop control design for redundant systems is, however, a challenging topic, especially for strongly dynamic tasks like hopping. In this work, we test the abilities of the SEDMA by using it to actuate a single-leg hopping robot. Its controller features a closed-loop hopping controller and a control allocator, which minimizes the electrical energy consumption of the SEDMA. Tests on a physical setup prove that the actuator and its online controller are able to generate consistent hopping patterns. The work highlights the difficulties in achieving optimality in online control when the internal dynamics of kinematically redundant actuators become relevant.
CRIS-Team Scopus Importer:2021-09-24
Keywords: compliance and impedance control; Legged robots; motion control; optimization and optimal control